2017
DOI: 10.18632/oncotarget.18200
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific molecular alterations are associated with metastatic clear cell renal cell cancer progressing under tyrosine kinase inhibitor therapy

Abstract: The availability of tyrosine kinase inhibitors (TKI) during the past ten years has led to improved response and overall survival of patients suffering from metastatic clear cell renal cell carcinoma (ccRCC). However, most of these tumors will eventually progress due to resistance evolving under therapy. The objective of this pilot study was to determine whether molecular alterations in ccRCC tissues sampled over the course of the disease might be suggestive of potential therapies. We performed whole exome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Significant molecular heterogeneity was also detected between primary and metastatic lesions, with only a small subset of alterations present in both sites. In one study, post-sunitinib metastatic lesions carried mutations in FLT4, KMT2D, and BMP5, which were not detected in the primary tumor (90). Studies by Hatiboglu et al demonstrated that although neoadjuvant treatment with sorafenib was clinically active in downsizing tumors in patients with locally confined, non-metastatic ccRCC, such treatment led to an enhanced functional ITH in the residual tumor tissue (91).…”
Section: Mechanisms Of Primary and Acquired Resistance To Systemic Thmentioning
confidence: 99%
“…Significant molecular heterogeneity was also detected between primary and metastatic lesions, with only a small subset of alterations present in both sites. In one study, post-sunitinib metastatic lesions carried mutations in FLT4, KMT2D, and BMP5, which were not detected in the primary tumor (90). Studies by Hatiboglu et al demonstrated that although neoadjuvant treatment with sorafenib was clinically active in downsizing tumors in patients with locally confined, non-metastatic ccRCC, such treatment led to an enhanced functional ITH in the residual tumor tissue (91).…”
Section: Mechanisms Of Primary and Acquired Resistance To Systemic Thmentioning
confidence: 99%
“…1 Although many treatments are available for patients with advanced RCC, complete and durable tumor responses have not been achieved in the majority of patients, probably because of intratumor heterogeneity and diverse mechanisms of drug resistance leading to tumor growth. [2][3][4][5][6][7][8] Thus, the development of new agents and combination therapies to improve clinical outcome is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Dicha prueba evalúa de manera simultánea las mutaciones en diferentes genes, incluyendo el EGFR, reordenamientos en el gen de la ALK, genes B-Raf (BRAF), ROS-1, K-RAS, MET y HER2 y varias otras moléculas que regulan diferentes vías de traducción de señales como son las vías de MAP cinasas o PI3K-AKT-MTOR. 16 Hasta el momento la FDA ha aprobado diversos TKI contra los siguientes blancos terapéuticos: EGFR, BRAF, ROS1 y ALK. 17 Varias mutaciones genéticas se han identificado como posibles blancos terapéuticos.…”
Section: Discussionunclassified